In Our Backyard: Perceptions About Fracking, Science, and Health by Community Members. (May 2020) - McElroy, Jane A.; Kassotis, Christopher D.; Nagel, Susan C.
Unconventional oil and gas (UOG) extraction (fracking) has increased in the United States, as well as interest in the associated risks and benefits. This study's purpose was to qualitatively examine residents' perceptions about UOG development in their community. Fifteen interviewees involving residents of Garfield County, Colorado, a drilling-dense region, were transcribed and analyzed. The study found six themes: (1) health concerns, both human and animal, (2) power struggles between government and industry/between industry and residents, and (3) perception and some acceptance of increased risk. Less common themes were (4) reliance on science to accurately determine risk, (5) frustration with potential threat and loss of power, and (6) traffic and safety concerns. Community perceptions of UOG development are complex, and understanding the position of community members can support the need for additional public health research and impact assessments regarding community exposures from UOG drilling operation exposures.